Liquid lime: effect on soil chemical properties and wheat grain yield - Beutler, Amauri Nelson (2015)
Brazilian soils are usually acid and require correction to provide high yields. To this end, milled lime, in powder form, has been used effectively for decades. Recently, liquid lime was proposed for both acidity correction and supply of Ca2+ and Mg2+. The aim of this study was to evaluate the effect of liquid lime on soil chemical properties and wheat grain yield. The experimental design was completely randomized with five treatments and four replications, with 3 × 4 m (12 m2) plots. The treatments were levels of 0, 5, 10, 20 and 40 L ha -1 of liquid lime applied to the soil surface in March 2013 with a nozzle array and liquid sprayer rate of 160 L ha -1 . Soil chemical properties were evaluated after 30 days. In June, wheat was sown. In harvest were evaluated wheat shoot dry matter, mass of 100 grains and grain yield in 2 m2 area. Liquid lime up to a level of 40 L ha -1 did not improve soil chemical properties and wheat grain yield.